Indole-3-carbinol attenuates the deleterious gestational effects of bisphenol A exposure on the prostate gland of male F1 rats - Brandt, Joyce Zalotti [UNESP]; Silveira, Livia Teresa R. [UNESP]; Grassi, Tony Fernando [UNESP]; Anselmo-Franci, Janete A.; Favaro, Wagner Jose; Felisbino, Sergio Luis [UNESP]; Barbisan, Luis Fernando [UNESP]; Scarano, Wellerson Rodrigo [UNESP] (Elsevier B.V., 2014)
Bisphenol A (BPA) is a chemical that has been investigated for it potential to cause prostate diseases. In this study, pregnant Sprague-Dawley rats were treated with 25 or 250 mu g/kg BPA from gestational day (GD) 10 to GD21 with or without concurrent indole-3-carbinol (I3C) feeding. I3C is a phytochemical, and it affords chemoprotection against many types of neoplasia. Male F1 rats from different litters were euthanized on post-natal day (PND) 21 and PND180. BPA-treated groups showed a significant increase in histopathological lesions, but I3C feeding reversed many of these changes, mainly at PND180. Maternal I3C feeding increased prostate epithelial apoptosis in the BPA-treated groups and across age groups. Furthermore, I3C induced partial normalization of the prostate histoarchitecture. The results pointed to a protective effect of maternal I3C feeding during pregnancy in the BPA-exposed male offspring, thereby indicating reduction in the harmful effects of gestational BPA imprinting on the prostate. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Bisphenol A; Prostate; Inflammation; Indole-3-carbinol; Chemoprevention; Reproductive toxicology